ROAD TRAFFIC OFFENSES IN THE CZECH REPUBLIC, POINT SCORING SYSTEM OF DRIVERS IN THE CZECH REPUBLIC, GERMANY AND POLAND AND SOLUTIONS OF TRAFFIC OFFENSES BY THE POLICE OF THE CZECH REPUBLIC AND AT THE MUNICIPAL DEPARTMENT WITH EXTENDED POWERS (Perner's Contacts, 2021)
The paper presents the basic legal regulations of the EU and the legal regulations of the Czech Republic regulating the area of ​​traffic accidents and traffic offences in road transport. It indicates the main traffic offense, which is exceeding the speed limit. It briefly analyses the statistics of traffic accidents in the Czech Republic in relation to the statistics of traffic offenses in road transport nationwide as well as in a selected municipality with extended powers. The paper comments and compares point scoring systems in the Czech Republic, Germany and Poland. This comparison is based on selected traffic offences. It describes the procedure of the Police of the Czech Republic and the technological procedure at the municipal department of the municipality with extended powers for processing the driver's offense. The article proposes specific changes in processing by the Police of the Czech Republic and the municipal department of a municipality with extended powers. These changes should lead to faster processing of the offense, rationalization of the work of the Official and also to higher awareness of the driver who committed the offense.
Keywords: point scoring system of drivers; traffic accidents; traffic administration agendas; municipal department of the municipality with extended powers; fines; road traffic offenses; driving ban